Post-exposure prophylaxis for Middle East respiratory syndrome in healthcare workers. Issue 1 (January 2019) - Park, S.Y.; Lee, J.S.; Son, J.S.; Ko, J.H.; Peck, K.R.; Jung, Y.; Woo, H.J.; Joo, Y.S.; Eom, J.S.; Shi, H.
Summary: An effective post-exposure prophylaxis (PEP) strategy may limit the spread of infection. However, there is no consensus regarding PEP for Middle East respiratory syndrome coronavirus (MERS-CoV) infection. This study assessed the efficacy of ribavirin and lopinavir/ritonavir as PEP for healthcare workers (HCWs) exposed to patients with severe MERS-CoV pre-isolation pneumonia. The safety of the PEP regimen was assessed. HCWs with high-risk exposure to MERS-CoV pre-isolation pneumonia were retrospectively enrolled. HCWs who received PEP therapy were classified into the PEP group. PEP therapy was associated with a 40% decrease in the risk of infection. There were no severe adverse events during PEP therapy.